2016
DOI: 10.1097/fjc.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Platelet Response to Clopidogrel in Abcc3-deficient Mice Due to Its Increased Bioactivation

Abstract: Resistance of the patient to clopidogrel (an inactive prodrug) has been recently reported to be associated with increased messenger RNA expression of ABCC3 that encodes MRP3 (multidrug resistance-associated protein 3). However, there is no evidence showing the effects of MRP3 on altered platelet responses to clopidogrel and their underlying mechanisms. To further clarify whether the presence or absence of Mrp3 could affect the formation of and response to clopidogrel active metabolite (CAM) in Abcc3 knockout (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…A pilot clinical research study indicated that patients with low ABCC3 mRNA expression would respond well to clopidogrel and vice versa (Luchessi et al, 2012). Consistent with this finding, we observed that the Abcc3 knockout (KO) mice exhibit an enhanced platelet response to clopidogrel due to increased CAM formation when compared with wild-type (WT) mice (Tai et al, 2016).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…A pilot clinical research study indicated that patients with low ABCC3 mRNA expression would respond well to clopidogrel and vice versa (Luchessi et al, 2012). Consistent with this finding, we observed that the Abcc3 knockout (KO) mice exhibit an enhanced platelet response to clopidogrel due to increased CAM formation when compared with wild-type (WT) mice (Tai et al, 2016).…”
Section: Introductionsupporting
confidence: 81%
“…The concentrations of clopidogrel, CAM, CLP-C, and CLP-G in plasma and liver tissue as well as piroxicam (IS) were determined by the validated LC-MS/ MS method as described elsewhere (Tai et al, 2016;Yin et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…immediate derivatization with MPB as described elsewhere (Tai et al, 2016;. Plasma was separated after centrifugation at 1,960× g for 10 min and stored at −80°C until analysis.…”
Section: What Is the Clinical Significancementioning
confidence: 99%
“…The samples were prepared as described previously (Jia et al, 2018;Tai et al, 2016; with slight modifications. In brief, an aliquot of 10 μl plasma was spiked with 100-μl acetonitrile (containing 10-ng•ml −1 piroxicam as IS) and then vortex-mixed for 3 min for protein precipitation.…”
Section: Sample Preparationmentioning
confidence: 99%